The role of hours changes for the increase in German earnings inequality - Biewen, Martin; Plötze, Daniela (Bonn, 2018)
"Using data from the German Structure of Earnings Survey (GSES), this paper studies the role of changes in working hours for the increase in male and female earnings inequality between 2001 and 2010. We provide both classic decompositions of the variance of log earnings into the variances of hours, wage rates and their covariance, and decompositions based on reweighting the conditional hours distribution. Depending on the inequality measure considered, our results suggest that between 10 and 30 percent of the increase in male earnings inequality and 37 to 47 percent of the increase in female earnings inequality can be explained by changes in working hours. In addition, a large part of the inequality increase can be accounted for by changes in the composition of person and firm characteristics."